A multi-terrain spherical amphibious robot for on-land, in-water, and underwater operation - Nilas, P.; Ngo, T. (My University, 2019)
This paper presents an innovative multi-terrain amphibious robot that imitates the amphibian animals' locomotion ability for both onshore and offshore performances. The robot can roll on-land, swim in-water, submerge underwater, and crawl on the sea floor. The robot consists of a spherical body and an outer jacket shell with multiple tiny channels that function similar to the wheel tread while on-land and perform as the paddle when in-water. The proposed robot have superior capability that other conventional robots could not achieve. The robot could travel on multiple terrains such as rolling on soft ground, floating in-water, and maneuvering underwater. This research utilizes the Omni-directional wheel, and the propeller system for locomotion and movement control. The proposed system has been implemented to develop a prototypical multi-terrains amphibious robot, and the initial experimental results also demonstrate the capability of such a robot design.
Keywords: Amphibious robot; Aquatic robot; Mobile robot; Robot design and development